Validation of a Modified Submaximal Balke Protocol to Assess Cardiorespiratory Fitness in Individuals at High Risk of or With Chronic Health Conditions—A Pilot Study - Eike, Gert Sander Hamre; Aadland, Eivind; Blom, Ellen Eimhjellen; Riiser, Amund (Frontiers in Sports and Active Living, 2021)
Objectives: To validate a submaximal treadmill walking test for estimation of maximal oxygen consumption (V̇O2max) in individuals at high risk of or with chronic health conditions. Method: 18 participants (age 62 ± 16 years; V̇O2max 31.2 ± 5.9 mL·kg-1·min-1) at high risk of getting or with established chronic diseases performed two valid modified Balke treadmill walking protocols, one submaximal protocol and one maximal protocol. Test duration, heart rate (HR) and rate of perceived exertion (RPE) was measured during both tests. V̇O2max was measured during the maximal test. V̇O2max was estimated from the submaximal test by multiple regression using time to RPE ≥ 17, gender, age and body mass as independent variables. Model fit was reported as explained variance (R2) and standard error of the estimate (SEE). Results: The model fit for estimation of V̇O2max from time to RPE ≥ 17 at the submaximal test, body mass, age and gender was R2 = 0.78 (SEE = 3.1 mL·kg-1·min-1, p ≤ 0.001). Including heart rate measurement did not improve the model fit. Conclusions: The submaximal walking test is feasible and valid for assessing cardiorespiratory fitness in individuals with at high risk of or chronic health conditions.